OPPRESSION IN ANNE BRONTE’S AGNES GREY - Yuliska Bakia; Tini Mogea; Rinny Rorimpandey (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to demonstrate the presence of oppression in Agnes Gray by Anne Bronte. Compiled using qualitative research methods, namely research methods that present data and the results are presented in the form of words in the form of quotations. In addition, to examine how oppression in this novel is conducted research using objective approach theory. An objective approach is an approach that makes the literary work itself a single object by ignoring external factors that influence it Using the aforementioned methodology, the findings of this study demonstrate that the oppression shown in Anne Bronte's Agnes Gray alludes to a variety of oppressions, including brutality, exploitation, marginalization, helplessness, and cultural imperialism. Realizing the shortcomings in this study, the researcher hopes that further research that has the same research object will be even better. And with this research it is hoped that attitudes that refer to acts of oppression can become an important reference for us